Ballads in Oral and Written Tradition: Retrospective Research Survey - Liugaitė-Černiauskienė, Modesta (Tautosakos darbai, 2018)
The article aims at reviewing the rich and ambivalent Western folk ballad research tradition in terms of confluence of the oral and written traditions. Although being well-reflected in the West, this approach is hardly at all present in Lithuania. The article starts with discussing such cultural phenomenon as broadside ballads. In surveying them, the author maintains that popular publications of the 16th–19th century Europe (bibliothèque bleue, skyllingtricker, Volksbuch, pliegos de cordel, лубочная литература, etc.) were an inherent part of the folk culture. Printed sheets of folksongs and ballads used to be popular in Great Britain, the Netherlands, France, Italy, Spain, Germany, and subsequently in America. However, although spread and promoted by the press, the ballads hardly ascended the field of interest of the educated elite, remaining instead in the “lower” spheres of the popular culture.The first collectors of ballads from the 18th century (the “antiquarian period”) paid little attention to the sources of their material, being instead very keen on improving and elaborating of the ballad texts, and presenting them as creative manifestations of the “original bard” or the “national muse”. After the collections by Thomas Percy and Walter Scott appeared, William Motherwell turned back to the still thriving ballad tradition. This Scottish scholar, followed by his Danish colleague Svend Grundtvig and the American Francis James Child founded the modern ballad folklore research, since their collections represented the oral folk tradition rather than engaging in search for the “original” folk ballads. The subsequent researchers, influenced by the Child’s ballad scholarship (Phillips Barry, Cecil J. Sharp, Olive D. Campbell, Louise Pound, Henry M. Belden, etc.), continued investigating the American ballad legacy. However, while collecting and encouraging to further collect the surviving ballads they increasingly realized the huge distance between their endeavors and the Child’s collection. The heterogeneous and fragmented nature of the ballads from the oral tradition was increasingly recognized and acknowledged, along with unavoidable impact of the written and printed sources.Barre J. Toelkien, the scholar belonging to even later generation, attempted methodical indexing of the oral ballads belonging to the Child’s collection. Dianne M. Dugaw in turn suggested that assuming the non-written songs, those from the oral tradition, being inherently different from the printed ones had largely affected the way in which folklore researchers perceived and interpreted folksongs. She concluded that differences devised between the written and non-written, between commercial and non-commercial forms were frequently just illusive, since commercial dissemination constituted an integral part of the folksongs development.In view of the confluence of the oral and written traditions surveyed in this article, it is reasonable to conclude that written culture, or rather the popular press, constituted a significant factor affecting the existence of folk ballads in the West; because of obvious reasons, such culture was absent in old-time Lithuania. Contrary to Lithuania, the ballad tradition of the West was nurtured by the written and printed sources. Therefore, the Lithuanian case could present a kind of thought experiment to the folklore researcher, vividly illustrating the plausible ballad tradition development in the West, if it could be unaffected by such phenomena as printed texts in native languages, readily available to the common people.
Keywords: -